(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This article provides a comprehensive exploration of the essential concepts surrounding the modification of morphemes in linguistics. It delves into the fundamental role played by morphemes as the building blocks of words, elucidating the distinction between free and bound morphemes. The piece effectively outlines various processes of morpheme modification, including prefixation, suffixation, infixation, reduplication, and conversion, shedding light on how these processes alter the meaning and grammatical function of words. Moreover, the article goes beyond mere description, offering insightful commentary on the cultural and linguistic variations in morpheme modification across different languages. It emphasizes the diverse ways in which languages employ these processes, highlighting examples from various linguistic typologies to illustrate the differences in word formation strategies.